Liquid Crystal Elastomer with Integrated Soft Thermoelectrics for Shape Memory Actuation and Energy Harvesting. Issue 23 (2nd May 2022) - Zadan, Mason; Patel, Dinesh K.; Sabelhaus, Andrew P.; Liao, Jiahe; Wertz, Anthony; Yao, Lining; Majidi, Carmel
Abstract: Liquid crystal elastomers (LCEs) have attracted tremendous interest as actuators for soft robotics due to their mechanical and shape memory properties. However, LCE actuators typically respond to thermal stimulation through active Joule heating and passive cooling, which make them difficult to control. In this work, LCEs are combined with soft, stretchable thermoelectrics to create transducers capable of electrically controlled actuation, active cooling, and thermal‐to‐electrical energy conversion. The thermoelectric layers are composed of semiconductors embedded within a 3D printed elastomer matrix and wired together with eutectic gallium–indium (EGaIn) liquid metal interconnects. This layer is covered on both sides with LCE, which alternately heats and cools to achieve cyclical bending actuation in response to voltage‐controlled Peltier activation. Moreover, the thermoelectric layer can harvest energy from thermal gradients between the two LCE layers through the Seebeck effect, allowing for regenerative energy harvesting. As demonstrations, first, closed‐loop control of the transducer is performed to rapidly track a changing actuator position. Second, a soft robotic walker that is capable of walking toward a heat source and harvesting energy is introduced. Lastly, phototropic‐inspired autonomous deflection of the limbs toward a heat source is shown, demonstrating an additional method to increase energy recuperation efficiency for soft systems. Abstract : A liquid crystal elastomer (LCE) thermoelectric device is reported, which combining active Peltier heating and cooling of LCE, along with environmental and regenerative Seebeck energy harvesting in a 3D printed material architecture. A new method of actuating LCEs, along with a new, more efficient approach to soft robotics, is introduced.